Outcome of Thromboembolic Events and Its Influence on Survival Time of Advanced NSCLC Patients Treated with Antiangiogenic Therapy - Ou WF; Liao PY; Hsu YW; Huang YH; Hsu KH; Tseng JS; Chang GC; Yang TY (Cancer Management and Research, 2023)
Wei-Fan Ou,1 Pei-Ya Liao,1 Yu-Wei Hsu,2,3 Yen-Hsiang Huang,1,4– 6 Kuo-Hsuan Hsu,6,7 Jeng-Sen Tseng,1,4– 6,8 Gee-Chen Chang,4,9– 11 Tsung-Ying Yang1,6,12 1Division of Chest Medicine, Department of Internal Medicine, Taichung Veterans General Hospital, Taichung, Taiwan; 2Cancer Prevention and Control Center, Taichung Veterans General Hospital, Taichung, Taiwan; 3Computer and Communications Center, Taichung Veterans General Hospital, Taichung, Taiwan; 4Institute of Biomedical Sciences, National Chung Hsing University, Taichung, Taiwan; 5College of Medicine, National Yang Ming Chiao Tung University, Taipei, Taiwan; 6Lung Cancer Comprehensive Care and Research Center, Taichung Veterans General Hospital, Taichung, Taiwan; 7Division of Critical Care and Respiratory Therapy, Department of Internal Medicine, Taichung Veterans General Hospital, Taichung, Taiwan; 8Department of Post-Baccalaureate Medicine, College of Medicine, National Chung Hsing University, Taichung, Taiwan; 9Division of Pulmonary Medicine, Department of Internal Medicine, Chung Shan Medical University Hospital, Taichung, Taiwan; 10School of Medicine, Chung Shan Medical University, Taichung, Taiwan; 11Institute of Medicine, Chung Shan Medical University, Taichung, Taiwan; 12Department of Life Sciences, National Chung Hsing University, Taichung, TaiwanCorrespondence: Jeng-Sen Tseng, Lung Cancer Comprehensive Care and Research Center, Taichung Veterans General Hospital, No. 1650, Sect. 4, Taiwan Boulevard, Taichung, 407, Taiwan, Tel +886-4-23592525 ext. 3232, Fax +886-4-23741320, Email tzeng64@gmail.comBackground: Antiangiogenetic therapy and lung cancer, per se, are associated with an increased risk of thromboembolic events (TE). We aim to evaluate the pattern and outcome of TE as well as its influence on survival time of advanced non-small cell lung cancer (NSCLC) patients receiving antiangiogenic therapy.Methods: This was a retrospective cohort study, which included advanced NSCLC patients receiving antiangiogenic therapy. All TE were confirmed by objective image studies. We disclosed the presentation and risk factors of TE and evaluated its influence on outcome.Results: A total of 427 patients were included. TE occurred in 43 patients (10.1%). Deep vein thrombosis (DVT) was the most common TE (n = 20). Up to 46.2% of DVT did not occur in the typical lower extremities. Two patients died of TE. Among patients with continuous use or reuse of antiangiogenetic therapy, 18.2% had recurrent TE events. At the occurrence of TE, 28 patients experienced progressive disease (TE with PD), while tumor status remained stable in another 15 patients (TE without PD). The post-TE survival of patients without and with PD were 8.9 months (95% CI 3.9– 13.9) vs 2.2 months (95% CI 0.1– 4.3), P = 0.012. As compared with patients without TE (31.4 months [95% CI 27.1– 35.7]), TE with PD patients experienced a significantly shorter overall survival (20.1 months [95% CI 15.5– 24.6]), but TE without PD patients had comparable survival time (32.7 months [95% CI 7.4– 28.1]) (P = 0006). The use of hormone analogue and proteinuria predicted the events among TE with PD group (aOR 2.79 [95% CI 1.13=6.92]; P = 0.027) and TE without PD group (aOR 4.30 [95% CI 1.13– 16.42]; P = 0.033), respectively.Conclusion: Owing to the different risk factors and influences on the survival time, TE with and without PD may be two different disease entities.Keywords: non-small cell lung cancer, NSCLC, antiangiogenesis, bevacizumab, ramucirumab, thromboembolism